2017
DOI: 10.1128/jvi.01554-16
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Efficacy of Measles Virus Fusion Protein-Derived Peptides Is Modulated by the Properties of Self-Assembly and Membrane Residence

Abstract: Measles virus (MV) infection is undergoing resurgence and remains one of the leading causes of death among young children worldwide despite the availability of an effective measles vaccine. MV infects its target cells by coordinated action of the MV hemagglutinin (H) and fusion (F) envelope glycoproteins; upon receptor engagement by H, the prefusion F undergoes a structural transition, extending and inserting into the target cell membrane and then refolding into a postfusion structure that fuses the viral and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
85
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(91 citation statements)
references
References 83 publications
6
85
0
Order By: Relevance
“…4 and 5), suggesting that these two lipids tether HR2 peptides near viruses throughout their endocytosis. That lipid conjugations allow HR2 peptides to accumulate in endosomes, thereby blocking "slow"-entering viruses, has been recently documented (Figueira et al, 2016;Lee et al, 2011), and is again shown here with the CoVs. However, when the virus entry was accelerated, through TMPRSS2 overexpression, the cholesterol-conjugated HR2 lost much , 10 µM E64d, or 100 nM bafilomycin A1 (BafA1) for 1 h, then transduced with WT or S2′ mutant (S2′ mut) MERS pps, without removing previously applied inhibitors.…”
Section: Discussionsupporting
confidence: 66%
“…4 and 5), suggesting that these two lipids tether HR2 peptides near viruses throughout their endocytosis. That lipid conjugations allow HR2 peptides to accumulate in endosomes, thereby blocking "slow"-entering viruses, has been recently documented (Figueira et al, 2016;Lee et al, 2011), and is again shown here with the CoVs. However, when the virus entry was accelerated, through TMPRSS2 overexpression, the cholesterol-conjugated HR2 lost much , 10 µM E64d, or 100 nM bafilomycin A1 (BafA1) for 1 h, then transduced with WT or S2′ mutant (S2′ mut) MERS pps, without removing previously applied inhibitors.…”
Section: Discussionsupporting
confidence: 66%
“…σ suggests the derivatized peptide may self-associate in membranes, which may be the basis of complex dissociation kinetics. Additionally, HRC4 is able to self-assemble in solution44. We modified equation (S24) to account for two distinct peptide populations, either monomeric or aggregated, for instance, and adequately fitted the resulting equation (1) to the dissociation data (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We replaced the traditional PEG flexible linker with dPEG so that chain length can be modulated at the stage of peptide synthesis [31]. For comparison with the cholesterol moiety used in the prototype VIKI-PEG 4 -Chol peptide we studied tocopherol (Table 1), because tocopherol's specific interaction with membranes may improve the biophysical characteristics of the lipopeptide [12].…”
Section: Glycoprotein Mediated Cell-cell Fusionmentioning
confidence: 99%
“…We compared the efficacy of VIKI-dPEG4-Chol and VIKI-dPEG4-Toco against NiV in hamsters ( Figure 2). We previously determined an LD [32] and established pharmacokinetics and biodistribution of HRC-derived peptides in hamsters and mice [11,12,17]. In this study, we determined the appropriate dose to target both upper and lower respiratory tract after i.n.…”
Section: Peptide Inhibition Of Nipah Virus Infection In Hamstersmentioning
confidence: 99%
See 1 more Smart Citation